Bibliographic Reception of Reinhart Koselleck's Work in Peru: 2000-2020 - Carrillo, Ricardo L. Falla (Journal of Posthumanism, 2025)
This article examines the reception and influence of German historian Reinhart Koselleck's work in Peru between 2000 and 2020. Known for his focus on conceptual history, which traces the evolution of key political and social concepts, the study explores how Peruvian scholars have adopted and adapted his methodology to analyze the country's political and social history. Drawing on a systematic literature review, the article identifies key themes, findings, and implications, assessing the contributions of Koselleck's conceptual history to enriching historical analysis in Peruvian contexts. The study emphasizes interdisciplinarity and methodological adaptations as essential tools for understanding Peru's historical and cultural complexities.